FAMILY FRIENDLY ICU QUALITY ORIENTED WITH EMIL MODEL: STUDY AT RSUP DR. M. DJAMIL PADANG - Emilzon Taslim; Afrizal; Tinni Trihartini Maskoen; Yusirwan Yusuf; Almh. Ike Sri Redjeki (Bajang Institute, 2022)
This study aims to determine the culturally competent family-friendly ICU model on ICU service satisfaction. This research was conducted in April-December 2021 at Dr. RSUP. M. Djamil Padang. The research design used Quantitative Research Methods. The results showed that there was a relationship between satisfaction with information and satisfaction with service quality (p = 0.001), there was a relationship between satisfaction with comfort and satisfaction with service quality (p = 0.002) and there was a relationship between satisfaction with spiritual needs with satisfaction with service quality (p= 0.001). The researcher concludes that information, comfort and spiritual needs greatly affect the quality of service in the ICU Dr. M. Djamil Padang